(untitled) (Journal of Analytical Oncology, 2021)
Introduction: The aim of this study was to investigate the rate and causes of re-hospitalization in the first 30 days after Hyper-CVAD chemotherapy in all patients with acute lymphoblastic leukemia. Methods: This descriptive, analytical and cross-sectional study was performed on 827 admissions in ALL patients aged 18 years and older with unplanned hospitalization after HyperCVAD chemotherapy in less than 30 days’ post chemotherapy from April 2016 to April 2018 in Hematology and medical oncology department. Results: The rate of unplanned re-admission was 9.91% in all patients. Mean follow-up time was 13.77 ± 6.26 months and the mean age of patients was 35.55 ± 14.6 years. Re-admission rate was more frequent in men (65.7%) and most patients were readmitted only once. The mean duration of re-admission was 8.2±4.15 days and most patients were re-admitted after cycles IB, IIIB and IVB of hyper-CVAD chemotherapy. The most common causes of readmission were febrile neutropenia and pancytopenia. Except for significant changes in CBC, no significant changes were observed in other laboratory tests. Urine culture and blood culture were reported positive in 13.6% and 31.57% respectively, and E-coli was the most common organism isolated from cultures. Conclusion: We found increased rate of re-admission following hyper-CVAD chemotherapy in patients with acute lymphoblastic leukemia which was due to side effects of chemotherapy regimen. It seems to be important not only for high rate of mortality and morbidity in patients resulting from this chemotherapy regimen, but also imposing the heavy cost on health system. Therefore, more effective preventive measures are necessary and useful.